Asyura: Antara Doktrin, Historis dan Antropologis Perspektif Dakwah Pencerahan - Prof. Dr. H. Ahmad Khairuddin, M.Ag (UIN Antasari Banjarmasin, 2015)
The month of Muharram is a holy month and precious in Islam that it can be seen from various perspectives. that is perspective of hadith (doctrine), historical perspective, and the perspective of culture (anthropological). Preferment specifically there on the 10th of Muharram is called as the day of Ashura. On the day that Muslims are highly recommended for fast and based on hammiyyah sunnah of the Prophet. also commanded on the ninth day called tasu'a. In some places, developing traditions and beliefs surrounding the Ashura who did not have a strong foundation. The developing tradition that should not to shift the conception of the primacy of Muharram and Ashura as described Prophet. in the traditions validity, especially the law of fasting Sunnah many ignored by most of the Islamic community itself. Keywords: Ashura, Doctrine, Historical, Anthropological and Da'wah